Platelets and Complement Cross-Talk in Early Atherogenesis - Kim, Hugh; Conway, Edward M. (Frontiers in Cardiovascular Medicine, 2019)
Atherosclerosis remains a ubiquitous and serious threat to human health. The initial formation of the atherosclerotic lesion (atheroma) is driven by pro-inflammatory signaling involving monocytes and vascular endothelial cells; later stages of the disease involve rupture of well-established atherosclerotic plaques, thrombosis and blood vessel occlusion. While the central role of platelets in thrombosis is undisputed, platelets exhibit pro-inflammatory acitivities and contribute to early-stage atheroma formation. Platelets also engage components of the complement system, an essential element of innate immunity that contributes to vascular inflammation. Here we provide an overview of the complex interplay between platelets and the complement system, with a focus on how the crosstalk between them may impact on the initiation of atheroma formation.